Cervical screening participation and access facilitators and barriers for people with intellectual disability: a systematic review and meta-analysis - Power, Rosalie; David, Michael; Strnadová, Iva; Touyz, Lauren; Basckin, Caroline; Loblinzk, Julie; Jolly, Heather; Kennedy, Elizabeth; Ussher, Jane; Sweeney, Sally; Chang, Ee-Lin; Carter, Allison; et al. (Frontiers in Psychiatry, 2024)
Background: The World Health Organisation’s vision of eliminating cervical cancer as a public health problem is achievable, but must include people with intellectual disability. A better understanding of cervical screening in the lives of people with intellectual disability is needed. This study systematically reviewed research on the rates of cervical screening among people with intellectual disability, and facilitators and barriers that affect participation. Method: Six electronic databases were searched: MEDLINE, CINAHL, Scopus, PsycINFO, Embase and Pro-Quest Central Social Sciences Collection. Empirical studies published between 1986 and 2023, in English language peer-reviewed journals were eligible. Further articles were identified through forward and backward citation tracking, and hand-searching two key journals. Two authors screened the studies, extracted the data, and collated study outcomes using a standardised software program. A meta-analysis was performed using the DerSimonian and Laird method to estimate pooled effect sizes in prevalence rates and odds ratios (ORs). The socio-ecological model was used to thematically analyse facilitators and barriers impacting cervical screening participation. Results: Sixty-three articles met the inclusion criteria. Of these, 42 reported rates of cervical screening participation and 24 reported facilitators or barriers to cervical screening. Overall, the studies reported a screening prevalence of 35% (95% CI: 26% to 45%), indicating that just over a third of people with intellectual disability have had cervical screening. The pooled odds ratio of 0.30 (95% CI: 0.23 to 0.41) indicated that people with intellectual disability are significantly less likely to have cervical screening compared with people without intellectual disability. Most studies examined individual and interpersonal factors impacting cervical screening. These included: (i) fear and anxiety among people with intellectual disability, (ii) misassumptions preventing screening participation, (iii) the role of support people, (iv) the need for education, (v) accessible information, and time to prepare for screening, (vi) patient-provider communication including challenges obtaining informed consent, and (vii) healthcare provider lack of confidence. Conclusion: Future research, policy and practice efforts must address barriers to cervical screening among people with intellectual disability and ensure these efforts are co-produced and community-led. This is critical to ensuring equity in global and local efforts to eliminate cervical cancer.